Effects of Muay Thai Practice on Self-Esteem, Body Perception, and Quality of Life in Adolescents with Overweight/Obesity - Saraiva, Bruna Thamyres Ciccotti [UNESP]; Henn, Rafael Rodrigues [UNESP]; Tebar, William Rodrigues [UNESP]; Dos Santos, Amanda Barbosa [UNESP]; Antunes, Ewerton Pegorelli [UNESP]; Ferrari, Gerson; Christofaro, Diego Giulliano Destro [UNESP] (Wolters Kluwer, 2024)
Introduction The aim of this study was to analyze the effects of 16 wk of Muay Thai practice on body perception, self-esteem, and quality of life in adolescents with overweight/obesity. Methods The sample consisted of adolescents with overweight/obesity, aged 10-17 yr. Overweight/obesity was confirmed using body mass index (BMI) and body fat (BF). Body mass and height were measured, from which BMI was calculated. BF was assessed using dual-energy x-ray absorptiometry. Body perception was measured using the Brazilian Silhouette Scale for Children, self-esteem was measured using the Rosenberg Self-Esteem Scale, and quality of life was measured using the 36-Item Short Form Health Survey. The Muay Thai intervention lasted 16 wk, with the initial 4 wk intended for adaptation and familiarization. Sessions were held three times per week on nonconsecutive days for 1.5 h. Protective equipment and devices, such as gloves, Thai pads, gauntlets, and head and rib protectors, were used. Training intensity was maintained between moderate and high according to the rate of perceived exertion scale. The control group did not perform any type of systematic training. Results There was a statistically significant group effect for self-esteem only (P < 0.01; effect size (η2) = 0.13). When analyzing η2, there was a group × time interaction in the pain domain of quality of life (P = 0.07; η2p = 0.11) considered medium to large. Furthermore, increases were observed in the prevalence of healthy self-esteem (before, 65.0%; after, 73.1%) and satisfaction with body image (before, 0%; after, 3.8%) in the Muay Thai group. Conclusion Muay Thai led to increased prevalences of individuals satisfied with their body image and with healthy self-esteem, as well as an increase in the pain domain score of quality of life in adolescents with overweight/obesity.